Transcriptomic and Metabolomic Differential Responses in Hypoxia on RBL-2H3 Cell Through Sodium Cromoglycate Mediates - Naser, Rana Hussein (Universitas Muhammadiyah Sidoarjo, 2024)
Hypoxia is a state in which sufficient oxygen is not available at the tissue level, a condition that leads to hypoxemia. Mast cells (MCs) are tissue resident cells that are widely distributed in vascularized tissues such as airways and gastrointestinal tract. Previously, studies have established the effect of pre-treatment of MCs with Sodium Cromoglicate (SCG) inhibitor in lung tissues of SD rats. Thus, due to the complexity and less understanding of the cell structure of lung tissues, and in order to understand the changes of MCs under hypoxia, RBL-2H3 were utilized in an experimental in-vitro study that aimed to evaluate the transcriptomic and metabolomic variations of these cells under hypoxic conditions and after pre-treatment with SCG. Differential expression analysis identified 25 genes as differentially expressed between HSCG vs HC group. On KEGG pathway enrichment analysis, Arachidonic acid metabolism, glutathione metabolism and AMPK pathway were among the enriched pathways in the HSCG vs HC group. A total of 1,513 metabolites were identified. These metabolites were amino acids, fatty acids, organic acids, lipids, carbohydrates, and others. Metabolic pathway enrichment analysis revealed that in the HSCG_vs_HC group, Glutathione, Val-Val, Arg-Glu, Pro-Glu and 1-Stearoyl-rac-glycerol were upregulated whereas, Cytidine, Hypoxanthine, Histamine and Pro-Asp were decreased. In conclusion, our study findings reveal that SCG impacts on cell mechanisms under hypoxic conditions.